Workload Analysis for Coating Operator in the Quality Control Department Using Cardiovascular Load and NASA-TLX Questionnaire - Kusmasari, Wyke; Candra, Nugraha Adi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT X produces cold-rolled steel coils, followed by a series of testing processes such as cutting, adhesive testing, and X-ray fluorescence (XRF) testing. These testing processes require significant time and effort and must be performed promptly. Additionally, the results need to be delivered on time. In the coating department, there is only one worker. This leads to complaints about the heavy workload, which can impact both the physical and mental health of the worker. Therefore, a workload analysis is necessary to achieve a more optimal performance evaluation. The methods used include cardiovascular load (CVL) measurement and the NASA-TLX questionnaire. The research results show a CVL value of 31.93%. The NASA-TLX score reached 88.75%, indicating a very high workload category. Proposed improvements to reduce physical workload include redesigning the rear part of the cutting machine by adding a trolley. Additionally, solutions to reduce mental workload include hiring additional workers at specific times or redistributing job tasks in the coating area.